The Allocation of Capital Between Residential and Nonresidential Uses: Taxes, Inflation and Capital Market Constraints - HENDERSHOTT, PATRIC H.; HU, SHENG CHENG (Journal of Finance, 1983)
ABSTRACT We have constructed a simple two‐sector model of the demand for housing and corporate capital. Economic growth and an increase in the inflation rate were then simulated with a number of model variants. The model and simulation experiments illustrate both the tax bias in favor of housing and the manner in which the increase in inflation between 1965 and 1978 magnified it. The existence of capital‐market constraints offsets the bias against corporate capital, but it introduces a sharp, inefficient reallocation of housing from less wealthy, constrained households to wealthy households who do not have gains on mortgages and are not financially constrained.